Evaluation of the effect of recycled waste plastic bags on mechanical properties of hot mix asphalt mixtures for road construction. Issue 1 (1st January 2021) - Assefa, Nakachew
ABSTRACT: An increase in population with a tremendous growth rate, the disposal of large amounts of non-decaying waste materials becomes a great concern in developing and developed countries. Also, due to an increase in traffic volumes and loading repetitions, surface distress was observed in most of the asphalt roads. Therefore, recycling waste plastic into a new product is a solution. A cleaned, dried, and grind waste plastic bag is introduced to the asphalt mixture from 6–18% with a 3% increment by the weight of optimum bitumen content for each nominal maximum aggregate size. A total, 171 Marshall and indirect tensile strength samples were prepared. From the test result, the optimum waste plastic bag replacement of 17, 13, and 7% are obtained for 9.5, 12.5, and 19 mm nominal maximum aggregate sizes respectively. From the comprehensive experimental results, its concluded that asphalt mixtures mixed with the optimum amount of waste plastic bag, Marshall stability and tensile strength ratio results can increase on average by 8 % and 4 % respectively. Stability, flow, bulk density, voids, and moisture susceptibility results satisfy the Ethiopian Road Authority minimum specifications.